2001
DOI: 10.1046/j.1526-0976.2001.52011-12.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Human Papillomavirus Among Adolescents

Abstract: Obstet Gynecol 2000;96:653–6 The purpose of this article was to determine what high‐school‐age adolescents know about HPV infection. A total of 523 inner‐city high school students completed a written survey that contained questions regarding HPV, STDs, and Pap smear screening. Over 87% of the study population claimed they had not heard of HPV. These students had considerably more knowledge about all other STDs. The students stated that school classes and media sources were their prime methods of gaining inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 0 publications
5
53
0
6
Order By: Relevance
“…A European study reported that only 17.7% of university students had heard about HPV (Lenselink et al, 2008). Slightly higher rates of awareness of HPV, approximately one-third, were reported from university students in the United States and Malaysia (Dell et al, 2000;Philips et al, 2003;Rashwan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A European study reported that only 17.7% of university students had heard about HPV (Lenselink et al, 2008). Slightly higher rates of awareness of HPV, approximately one-third, were reported from university students in the United States and Malaysia (Dell et al, 2000;Philips et al, 2003;Rashwan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in China, only 7.8% of women under 20 years old had heard about HPV (Li et al, 2009) while in Canada, only 13% of high school adolescents had heard about HPV, sexually transmitted diseases and pap test (Dell et al, 2000).…”
Section: Knowledge and Views Of Secondary School Students In Kuala Lumentioning
confidence: 97%
“…A lack of awareness of risk factors and prevention options is also believed to correlate with lower uptake (Waller et al 2004;Fylan 1998). Knowledge of cervical cancer and human papillomavirus (HPV) tends to be low overall, as various studies have shown (Baer et al 2000;Dell et al 2000;Klug et al 2005).…”
Section: Introductionmentioning
confidence: 99%